2019
DOI: 10.1007/s00277-019-03893-7
|View full text |Cite|
|
Sign up to set email alerts
|

The classic prognostic factors in advanced Hodgkin’s lymphoma patients are losing their meaning at the time of Pet-guided treatments

Abstract: The International Prognostic Score (IPS) is the most commonly used risk stratification tool for patients with advanced Hodgkin lymphoma (HL). It incorporates seven clinical parameters independently associated with a poorer outcome: male sex, age, stage IV, hemoglobin level, white blood cell and lymphocyte counts, and albumin level. Since the development of the IPS, there have been significant advances in therapy and supportive care. Recent studies suggest that the IPS is less discriminating due to improved out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…It should also be noted that, despite its historical importance, IPS has lost its prognostic value in the modern era using PET-guided therapy. 29 Nevertheless, it is also possible that a larger study may have captured the difference between the two treatment groups. In addition, our study used 6 cycles of BEACOPPesc, while 4 cycles has become the standard in PET2-negative patients since 2018.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that, despite its historical importance, IPS has lost its prognostic value in the modern era using PET-guided therapy. 29 Nevertheless, it is also possible that a larger study may have captured the difference between the two treatment groups. In addition, our study used 6 cycles of BEACOPPesc, while 4 cycles has become the standard in PET2-negative patients since 2018.…”
Section: Discussionmentioning
confidence: 99%
“…40 Bari et al recently published that NLR, LMR, and IPS did not retain any predictive value in the HD0801 trial in which patients with a positive PET-2 (defined as carrying Deauville score 3 or more) after two ABVD cycles underwent a more intense treatment with an early stem-cell transplantation and four cycles of IGEV (ifosfamide, gemcitabine, vinorelbine, prednisone) regimen. 41 Since IPS maintained its prognostic meaning in those trials in which the treatment of PET-2 positive was switched from ABVD to escBEACOPP patients, the authors concluded that the intensification treatment with autologous transplantation in PET-2-positive patients could justify the disappearance of any relevant prognostic factor at baseline, including IPS and NLR. The discrepancy with our results could also be due to the different patient evaluation at PET-2, since in the HD0801 patients with DS = 3 or more belonged to the PET-2-positive cohort, while in the HD0607 trial DS = 3 belonged to the PET-2-negative cohort, and the salvage regimen was more intensive in the study design of the HD0801 trial.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that PET2 assessments hold a superior prognosis potential to IPS [ 22 , 23 , 24 ]. There continues to be a debate surrounding the effectiveness of early‐response PET assessments to guide de‐escalation of therapy for patients with a high probability of cure after ABVD therapy and escalation for those at higher risk for treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, PET2‐driven strategies have certain limitations. PET scans are not always easily interpretable and PET2‐negative patients do not always display long‐term remissions [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%